A Journey to the Musée du quai Branly: The Anthropology of a Visit. (March 2017) - Debary, Octave; Roustan, Mélanie
Abstract: This article is an ethnographic account of visitors' reception of the Musée du quai Branly in Paris, France. The museum, opened in 2006 as part of a renewal of French ethnographic museums, presents works from Africa, the Americas, Asia, and Oceania that were collected in colonial contexts. Based on interviews and observations of museum staff and visitors, we describe the scenography as an invitation to a journey that leads visitors to feel a sense of disorientation. The visit raises important questions about art and material culture, which we explore in the second part about the nature of the objects. The museum proposes no answers nor provides any historical contextualization, with the effect being that the "others" have vanished. Their objects are conserved in a place where visitors simultaneously encounter "others" and their disappearance. In the museum's silence, its method of display constructs the way visitors establish the connection between the exhibition and French colonialism.